2005
DOI: 10.1253/circj.69.1568
|View full text |Cite
|
Sign up to set email alerts
|

Potent Capillary Isotachophoresis (cITP) for Analyzing a Marker of Coronary Heart Disease Risk and Electronegative Low-Density Lipoprotein (LDL) in Small Dense LDL Fraction

Abstract: apillary isotachophoresis (cITP) is a newly established technique for characterizing plasma lipoprotein subfractions according to their electric charges. It separates plasma lipoproteins into 8 fractions, comprising 3 high-density liporotein (HDL) fractions with fast (f), intermediate (I), and slow (s) electric mobility, a chylomicron/remnants fraction (fast very low-density lipoprotein (VLDL)), a VLDL/intermediate density lipoprotein (IDL) fraction (slow VLDL), 2 LDL fractions with fast and slow electric mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, as recently reviewed by Rivas-Urbina et al [13], a full spectrum of biological roles of electronegative LDL in various pathological conditions remains to be elucidated. Interestingly, it has been shown that the amount of electronegative LDL subfractions determined by capillary isotachophoresis correlates negatively with LDL particle size, thus suggesting that electronegative LDL is accumulated in the sdLDL fraction [14]. In addition, Zhang et al [15] demonstrated that rosuvastatin treatment significantly reduced the electronegative LDL contained in both large and sdLDL, thereby implying another pleiotropic effect of statins.…”
Section: Small Dense Ldl and Cardiovascular Riskmentioning
confidence: 99%
“…However, as recently reviewed by Rivas-Urbina et al [13], a full spectrum of biological roles of electronegative LDL in various pathological conditions remains to be elucidated. Interestingly, it has been shown that the amount of electronegative LDL subfractions determined by capillary isotachophoresis correlates negatively with LDL particle size, thus suggesting that electronegative LDL is accumulated in the sdLDL fraction [14]. In addition, Zhang et al [15] demonstrated that rosuvastatin treatment significantly reduced the electronegative LDL contained in both large and sdLDL, thereby implying another pleiotropic effect of statins.…”
Section: Small Dense Ldl and Cardiovascular Riskmentioning
confidence: 99%
“…Correct identification of patients with urothelial carcinoma from those with other malignant and nonmalignant genitourinary disease ranged from 86% to 100%. cITP has been used to search for a biomarker of coronary heart disease risk and electronegative low-density lipoprotein (LDL) in a small dense LDL fraction [55]. The electronegative LDL fraction decreased after treatment with fenofibrate.…”
Section: Cementioning
confidence: 99%
“…The same system was used to quantify charge-based low-density lipoprotein (LDL) subfractions, to examine the relation between insulin resistance and the ITP fast-migrating LDL levels [75], to determine three charge-based high density lipoprotein subfractions, and to investigate the effects of the inhibition of cholesteryl ester transfer protein activity by an inhibitor in Japanese white rabbits [76]. Also the same system was used to measure electronegative LDLs in the small dense LDL fraction [77] and a very similar system served for monitoring the changes in lipoprotein profile at hypertriglyceridemia [78].…”
Section: Analysis Of Lipoproteinsmentioning
confidence: 99%